Fatigue, executive function and psychological effects in children with immune thrombocytopenia: a cross‐sectional study. (24th January 2020) - Towner, Sarah; Berger, Zoe E.; Titman, Penny; New, Helen V.; Theodore, Kate; Brown, Gary; Sibson, Keith R.
Summary: Childhood ITP is often considered to be a relatively mild haematological disorder, with only a minority of patients requiring treatment for troublesome bleeding. Over recent years, wider effects of the condition have been identified in some adults, particularly relating to fatigue and cognitive impairment. In this study, we sought to investigate such effects in a group of children with ITP and further our understanding of their psychological profile. Children attending routine haematology outpatient clinics and their parents were asked to complete standardised questionnaires designed to assess a range of psychological and cognitive factors. Although the majority of children had some scores within the normal range, a significantly high proportion had difficulties with fatigue (70·6%), emotional and behavioural symptoms (25·7%) or executive functioning (19·4%). Quality of life and subjective evaluation of the illness (appraisal) correlated significantly with each of these domains, but bleeding severity and platelet count did not. Our findings provide valuable insight into the broader impact of childhood ITP, which could aid in providing holistic care, potentially contribute to decisions regarding medical treatment, and guide future research.